Novel Necropsy Findings Linked to Peracute Underwater Entrapment in Bottlenose Dolphins (Tursiops truncatus) - Epple, Alexandra L.; Daniel, Joanna T.; Barco, Susan G.; Rotstein, David S.; Costidis, Alexander M. (Frontiers in Marine Science, 2020)
Peracute underwater entrapment (PUE) is a recognized cause of death associated with anthropogenic trauma in marine mammals. We describe internal lesions likely resulting from extreme agonal exertion in bottlenose dolphins due to entanglement and forced submergence in fishing gear during PUE. We reviewed necropsy findings from bottlenose dolphins with known PUE statuses from Virginia, USA for 2016-2019 (n=31) for the presence of five lesions: pulmonary petechiae, pulmonary perivascular edema, hemorrhagic pulmonary lymph, separation of the rectus abdominis muscles, and acute abdominal hernias. Of the 31 cases, 23 were considered PUE cases due to the presence of external ligature marks consistent with entanglement in fishing gear. Of the animals examined, pulmonary perivascular edema, pulmonary petechiae and hemorrhagic pulmonary lymph were found in both PUE and non-PUE cases. Though found in 1 non-PUE case, pulmonary perivascular edema was significantly related to PUE. There was no significant relationship between PUE and pulmonary petechiae or hemorrhagic pulmonary lymph. Rectus abdominis muscle separations and acute abdominal hernias were only found in PUE cases and nine animals exhibited either one (n=7) or both (n=2) of the traumatic lesions. Although these two lesions were relatively rare, there was a statistically significant relationship between the presence of one or both of the lesions and positive PUE status. This study suggests that pulmonary perivascular edema, acute hernias and separations of the rectus abdominis muscles may be useful for diagnosing PUE in the absence of external fishery interaction lesions, and highlights the severity of agonal fisheries interactions.